Asymmetric Distributions of Auroral Kilometric Radiation in Earth's Northern and Southern Hemispheres Observed by the Arase Satellite. Issue 13 (6th July 2022) - Xiao, Fuliang; Tang, Jiawen; Zhang, Sai; Zhou, Qinghua; Liu, Si; He, Yihua; Yang, Qiwu; Kasahara, Yoshiya; Miyoshi, Yoshizumi; Kumamoto, Atsushi; Nakamura, Yosuke; Tsuchiya, Fuminori; et al.
Abstract: Auroral kilometric radiation (AKR) is generated at high latitudes and can propagate down to low latitudes. Due to the lack of direct observations, the characteristics of AKR in the middle and low latitudes of two hemispheres have not been studied so far. Here, using observations of the Arase satellite from 23 March 2017 to 31 July 2019, we present the first statistical study of AKR distribution in the northern (Magnetic latitude Mlat = 0°–40°) and southern (Mlat = −40°–0°) hemispheres. Results (totally 30, 353 samples) show that relatively high occurrence rates (>30%) of AKR in the northern (southern) hemisphere primarily stay in the region of magnetic local time MLT = 17–24 (MLT = 21–05). About 60% of wave samples in the northern (southern) hemisphere are observed in the frequency range of ≤300 kHz (>300 kHz). The asymmetric distribution in two hemispheres can further enrich our understanding of AKR. Plain Language Summary: Auroral kilometric radiation (AKR) is a strong radio emission with kilometric wavelength at the Earth. They have a potential for accelerating electrons to relativistic energies or scattering electrons into the atmosphere, leading to serious damage to spacecrafts or ozone destruction. Because the parallel electric field contributing to AKR generation should be different in the northern and southern hemispheres, it is necessary to study the distribution characteristics of AKR in two hemispheres. Here, we examine the data of Arase satellite from 23 March 2017 to 31 July 2019, and find that the distributions of AKR samples in two hemispheres are asymmetric. The occurrence rate in the southern hemisphere is greater than that in the northern hemisphere. More AKR samples in the northern (southern) hemisphere occur from dusk to midnight (pre‐midnight to dawn). More AKR samples in the northern (southern) hemisphere are observed in the frequency range of ≤300 kHz (>300 kHz). This study provides more information about AKR in the magnetosphere. Key Points: The distribution characteristics of Auroral kilometric radiation (AKR) in two hemispheres are presented for the first time based on observations from Arase satellite AKR samples in the northern (southern) hemisphere are observed relatively frequently in the region of magnetic local time = 17–24 (MLT = 21–05) More AKR samples in the northern (southern) hemisphere stay in the low (high) frequency range